KONSEP LA IKROHA FI AL-DIN DALAM Q.S AL-BAQOROH :256 KAJIAN ANALISIS TAFSIR MAQOSHID: 1. Pembahasan ayat dan terjemah 2. Analysis ke bahasa an 3. Azbabun Nuzul mikro dan makro 4. Pemahaman Tafsir maqoshid 5. Maqoshid lafadz la ikraha fiddin 6. Praktik maqoshid la ikraha fiddin - LATIFAHMULYANI (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2023)
Along with the development of the times, the human mindset is also growing. This also occurs in the perspective of humans in carrying out their beliefs, and some of them lead to acts of anarchy and religious bigotry. This paper attempts to explain the meaning of